Defence takes the floor! - Jurisdiction, concept of economic unity and protection of the weaker party - Manenti, Andrea (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The article tackles the evolution in the case law of the Court of Justice of the EuropeanUnion of the concept of economic unity starting from the recent Heineken judgment. The analysis isfocused particularly on the problems that the current general approach creates in relation to the burdenof proof in antitrust proceedings and the protection of the defense’s rights. In the end, considering theCourt of Justice established case law, the article examines – with some critical notes – how the conceptis used by national courts during the evaluation of their own jurisdiction.
Keywords: Private enforcement of EU competition law; Concept of economic unity; Jurisdiction in torts; Burden of proof